Why does ideological distance reduce public goods’ provision?; an explanation based on clientelistic employment - Gatica Arreola, Leonardo A. (Estudios de Economía, 2016)
This paper presents a model of political competition to explore the effect that the ideological distance between two political parties has over the provision of public goods. The main result argues that the ideological distance between parties and citizens has a negative relationship with the provision of public goods. In contrast with other models, the result is explained, neither by cooperation problems nor conflict between polarized groups, but because of the political profitability of clientelistic employment.